Immobilized-metal-ion affinity chromatography as a tool for the qualitative study of pepsinogen phosphorylation - Kucerová, Z; Majercaková, P (Journal of biochemical and biophysical methods, 2001)
Affinity chromatography on immobilized Fe(3+) ions--immobilized-metal-ion affinity chromatography (IMAC) method--was used for the determination of pepsin and pepsinogen phosphorylation. IMAC is a very powerful method for detailed studies of proteins. Dephosphorylation of the pepsinogens and pepsins has no effect on their proteolytic ability. For this reason, the determination of proteolytic activity was used for the detection of pepsinogen (pepsin) presence in the collected fractions as a very suitable and specific method. Pepsins and their zymogens probably have the same amounts of phosphate ions in their molecule. The exact definition of conditions is very important for the prepurification of the proteinases and for their analysis.
Keywords: Oligopeptides; Pepsinogen A; žaludeční sliznice; chromatografie iontoměničová; sekvence aminokyselin; Gastric Mucosa; Metals; indikátory a reagencie; železité sloučeniny; lidé; Chromatography, Gel; oligopeptidy; Buffers; kovy; Amino Acid Sequence; Indicators and Reagents; Phosphorylation; Ligands; Pepsin A; fosforylace; pepsin A; Chromatography, Affinity; gelová chromatografie; pufry; pepsinogen A; Chromatography, Ion Exchange; Ferric Compounds; chromatografie afinitní; ligandy; Humans